Penurunan Kecacatan di PT Mulcindo Steel dengan Pendekatan Filosofi Six Sigma - Punyawan, Shandy Ernanto; Rahardjo, Jani (Jurnal Titra, 2015)
PT Mulcindo Steel Industry is a company specialized in steel fabrication, service, forming products, hollow products, c-truss products, and galvanizing process. Defectâs percentages on c-truss, main runner, batten hat 28x17, metal runner, and mini furring are over 0,05% but the study will be focused on the highest percentage which is the c-truss with 0,11% defect percentage. DMAIC is used as a method to find problemâs root cause which is found by 5 why analysis. There were several suggestions which are product defective definitions, product quality characteristic socialization to employees, coil width checksheet monitoring, c-truss machine work instruction, straightening uncoiler to the machine. It is found that solution implementation can reduce the defect percentage in c-truss product to 0,073%. The result have been able to reduce the level of defect on the type of different âkupingan tidak samaâ.